Perspective Of Maslahah On The Distribution Of Zakat Funds By IZI Lampung For Humanitarian Programs - Jayusman, Jayusman; Novendri, Novendri; Shafra, Shafra; Bunyamin, Mahmudin (Universitas Islam Negeri Raden Intan Lampung, 2024)
This study analyzed the issues surrounding zakat distribution. The distribution of zakat is clearly stipulated in Islamic law, specifically in the Qur'an, Surah Al-Taubah, verse 60. The Inisiatif Zakat Indonesia (IZI) Lampung allocated zakat funds for disaster victims, such as those affected by earthquakes, tsunamis, landslides, and the COVID-19 pandemic. This study focused on the perspective of Maslahah regarding the distribution of zakat funds for humanitarian programs by IZI Lampung. The research was conducted as field research related to the distribution of zakat funds for humanitarian purposes. The primary data consisted of observations and interviews about the zakat distribution process for humanitarian programs. The data were analyzed using the Maslahah theory to draw conclusions. The findings indicated that the distribution of zakat funds for humanitarian programs by IZI Lampung was based on a prioritization scale, targeting the poor and needy. For natural disaster victims, IZI Lampung prioritized distribution to the worst-affected areas, coordinating with local governments. This approach brought significant benefits (Maslahah) to zakat recipients (mustahik), who included the poor, needy, debtors (gharimin), and those in the path of Allah (fî sabîlillâh).Keywords: IZI; Maslahah; Humanitarian; Zakat Fund Distribution